PENGGUNAAN E-LEARNING BERBASIS GOOGLE CLASSROOM SEBAGAI MEDIA PENDUKUNG DALAM PEMBELAJARAN MATEMATIKA DI MTs NEGERI TULEHU - Safarin Zurimi (STMIK KHARISMA Makassar, 2019)
E-learning learning media based on Google Clasroom can be translated as learning using electronic devices as the medium. E-learning is a set of applications and processes created for learning activities. The purpose of this study was to determine the use of e-learning media based on google classroom as supporting media in statistical material. This type of research used descriptive research with a quantitative approach. The instrument used in this study was a questionnaire to measure attitudes and levels of activeness, motivation and use of features in using google classroom, and interviews were used to obtain more in-depth information about factors that support and inhibit the use of google classroom media. Data about the use of google classroom learning media in this study were obtained from a questionnaire with a total of 12 statements using a Likert scale with a score of 1 to 4. This questionnaire was used to determine the level of use of the google classroom learning media from the activeness, ease and difficulty of accessing google classroom and motivation use of google classroom media which influences the level of use of google classroom media in the learning process in statistical subjects. Based on the results of data processing, it was found that through the implementation of e-learning based on google classroom, the learning outcomes of students with very good qualifications were 5 students namely 19.23%, 17 students with good qualifications were 65.4%, and 4 students with sufficient qualifications namely 15, 38%.